Dynamizations and Exchanges: Success Rates and Indications. Issue 12 (December 2015) - Litrenta, Jody; Tornetta, Paul; Vallier, Heather; Firoozabadi, Reza; Leighton, Ross; Egol, Kenneth; Kruppa, Christiane; Jones, Clifford B.; Collinge, Cory; Bhandari, Mohit; Schemitsch, Emil; Sanders, David; et al.
Abstract : Objective: To characterize the timing, indications, and "success rates of secondary interventions, dynamization and exchange nailing, in a large series of tibial nonunions" (dynamization and exchange nailing are types of secondary interventions). Setting: Retrospective multicenter analysis from level 1 trauma hospitals. Patients: A total of 194 tibia fractures that underwent dynamization or exchange nailing for delayed/nonunion. Intervention: Records and radiographs to characterize demographic data, fracture type, and cortical contact after tibial nailing were gathered. The radiographic union score for tibias (RUST) and the timing of intervention and time to union were calculated. Main Outcome Measures: The primary outcome was success of either intervention, defined as achieving union, with the need for further intervention defining failure. Other outcomes included RUST scores at intervention and union, and timing to intervention and union for both techniques. Two-tailed t tests and Fisher exact with P set at <0.05 for significance were used as indicated. Results: A total of 194 tibia fractures underwent dynamization (97) or exchange nailing (97). No statistical differences were found between groups with demographic characteristics. The presence of a fracture gap ( P = 0.01) and comminuted fractures ( P = 0.002) was more common in the exchange group. The success rates of the interventions and RUST scores were not different when performed before versus after 6 months; therefore, data were pooled. The RUST scores at the time of intervention were not different for successful or failed dynamizations (7.13 vs. 7.07, P = 0.83) or exchanges (6.8 vs. 7.3, P = 0.37). Likewise, the time to successful versus failed dynamization (165 vs. 158 days, P = 0.91) or exchange nailing (224 vs. 201 days, P = 0.48) was not different. No cortical contact or a gap was a statistically negative factor for both exchange nails ( P = 0.09) and dynamizations ( P = 0.06). When combined, the success in the face of a gap was 78% versus 92% when no gap was present ( P = 0.02). Conclusions: Previous literature has few reports of the success rates of secondary interventions for tibial nonunions. The indications for dynamization and exchange were similar. Comminuted fractures, and fractures with no cortical contact or "gap" present after intramedullary nailing, favored having an exchange nail performed over dynamization. Fracture gap was also found to be a negative prognostic factor for both procedures. Overall, this study demonstrates high rates of union for both interventions, making them both viable options. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.